2015
DOI: 10.1038/srep13926
|View full text |Cite|
|
Sign up to set email alerts
|

Facile Discovery of a Diverse Panel of Anti-Ebola Virus Antibodies by Immune Repertoire Mining

Abstract: The ongoing evolution of Ebolaviruses poses significant challenges to the development of immunodiagnostics for detecting emergent viral variants. There is a critical need for the discovery of monoclonal antibodies with distinct affinities and specificities for different Ebolaviruses. We developed an efficient technology for the rapid discovery of a plethora of antigen-specific monoclonal antibodies from immunized animals by mining the VH:VL paired antibody repertoire encoded by highly expanded B cells in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 43 publications
2
47
0
Order By: Relevance
“…Indeed, there are several reports where the predominant clones in a response have been shown to bind the antigen 103. In mice these experiments have been particularly successful 104. However, the assumption of largest clone providing best protection may be too simple, and many different immunoglobulin genes can respond to a single challenge.…”
Section: Clonality Analysismentioning
confidence: 99%
“…Indeed, there are several reports where the predominant clones in a response have been shown to bind the antigen 103. In mice these experiments have been particularly successful 104. However, the assumption of largest clone providing best protection may be too simple, and many different immunoglobulin genes can respond to a single challenge.…”
Section: Clonality Analysismentioning
confidence: 99%
“…This work helped reveal the structural similarities between different antibody solutions to broad V1/V2‐based HIV neutralization and outlined new strategies for V1/V2‐targeting vaccine designs. Paired V H :V L sequencing has also been applied to address several problems beyond HIV 56, 57…”
Section: Antibodyomics4mentioning
confidence: 99%
“…Interestingly, we found that antibodies isolated by yeast display from combinatorial libraries in which the V H and V L from spleen or bone marrow had been randomly paired were clonal relatives of antibodies identified via mining of the draining lymph node repertoire, and comprised authentic, natively paired, V H and V L sequences. Thus, in hyperimmune animals where antigen-specific antibodies comprise a significant portion of the repertoire, 29,[32][33][34][35] flow cytometric screening of libraries constructed via the random pairing of V H and V L genes can nonetheless result in the isolation of native antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…30,31 More recently, we have shown that antibody secreting B cells (CD138 C plasmablasts) within the draining lymph node are overwhelmingly antigen-specific, and that antibodies derived from these cells exhibit high binding affinity. 32 In this report, we sought to compare the isolation of highaffinity anti-ricin antibodies via mining of the draining lymph node repertoire and via yeast display of immune combinatorial libraries constructed from antibody mRNAs obtained from spleen or bone marrow cells. Overall, both approaches yielded strong ricin A chain binders (the lowest K d values were 0.97 and 0.58 nM, respectively, for these 2 methods).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation